The exchange rate exposure to Malaysian nonfinancial firms / Hanisah Miskam - Miskam, Hanisah (2007)
Financial theory predicts that a change in an exchange rate should affect the value of a firm or an industry. There are numerous studies which provide evidence for a relationship between foreign exchange movements and changes in firm values. This study will seek to estimate the sensitivity of Malaysian nonfinancial companies at the industry level over the period 2000-2006. It will focus on three selected industries which are construction, consumer products and hotel.